Analysis of Young Generations toward Stock Investment Intention: A Preliminary Study in an Emerging Market - Bagus Aditya Nugraha; Raden Aswin Rahadi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study attempts to analyze the young generations' perceptive variables in Indonesia, namely millennial (generation Y) and generation Z toward stock investment intention preliminarily.Design/Methodology/Approach: This study posits perceptive variables from the Theory of Planned Behavior (TPB) with various demographic characteristics as tablemoderating variables. This study utilized a structured online questionnaire survey to collect 64 samples and being analyzed by PLS-SEM. The group differences that being examined were investigated with multi-group analysis.Research findings: The findings from this study revealed that not all perceptive variables from TPB were significant on young Indonesian generations toward stock investment intention; only attitudes toward behavior had a significant effect. These findings were contrary to prior literature. Besides, Indonesia's young generations’ education level also played a moderating role in influencing stock investment intention. Theoretical contribution/Originality: This preliminary study provides potential facts regarding the applicability of the Theory of Planned Behavior in the emerging market (Indonesia) in stock investment intention.Practitioner/Policy implication: The practical contribution would be insights for policymaker and Securities Firms regarding young generations’ perspective on stock investment and what possible actions in terms of policies, programs, and campaigns that need to be done to increase the growth of investors’ number in Indonesia. For public firms, the insights could be useful in constructing sustainability strategies in terms of funding source from the firm’s stock.Research limitation/Implication: The sample used for this preliminary study was restricted to young generations divided into generation Y and Z from Indonesia only. This study focused on the fundamental implementation of TPB only; hence, the individual behavioral intention analysis was limited to TPB proxies. Since an online survey using a questionnaire was used to collect the data, the findings were limited and depending on the respondents’ answers regarding the issue.